Improving the Ability to Write News Texts Using the Studysaster Model with Event Photo Media in Grade VII Students of SMPN 4 South Kuta - Lukmanul Hakim, Fakhry; Suta Wardianto, Bayu; Salpa Riansi, Erwin (International Proceedings of Nusantara Raya, 2024)
This research aims to improve the ability to write news texts of students in grades VII-11 at SMPN 4 Kuta Selatan through the application of the Studysaster learning model combined with the use of event photo media. This class action research is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data was collected through writing ability tests, observation sheets, and interviews. The results show that the use of the Studysaster model with event photo media can significantly improve the ability to write news texts. The increase can be seen from the average score of students who increase in each cycle. In addition, students become more motivated and enthusiastic in learning to write because of the use of relevant and interesting event photo media. In conclusion, the Studysaster learning model with event photo media is effectively used as an alternative learning strategy to improve news text writing skills at the junior high school education level.